Laryngeal advancement surgery improves swallowing function in a reversible equine dysphagia model. (13th May 2015) - Virgin, J. E.; Holcombe, S. J.; Caron, J. P.; Cheetham, J.; Kurtz, K. A.; Roessner, H. A.; Ducharme, N. G.; Hauptman, J. G.; Nelson, N. C.
Summary: Reasons for performing study: Pharyngeal dysphagia is a debilitating, sometimes fatal condition in horses, with multiple aetiologies. The pathophysiology is complex and not fully understood. Treatment is largely supportive. Laryngeal advancement surgery may diminish symptoms of dysphagia and improve swallowing in affected horses. Objectives: 1) to induce reversible moderate and marked pharyngeal dysphagia by regional anaesthesia of branches of the glossopharyngeal (IX), vagus (X) and hypoglossal (XII) nerves; 2) to characterise the dysphagia produced by each model; and 3) to determine whether laryngeal advancement surgery improves swallowing in these models. Study design: Experimental design using 6 adult horses. Methods: Two dysphagia models were produced by blocking IX, the pharyngeal branch of X and XII unilaterally (moderate model) and only the pharyngeal branch of X bilaterally (marked model) within the guttural pouches. Both models were performed on each horse before and after surgery in order to assess the effectiveness of the surgical procedure as a potential treatment for pharyngeal dysphagia. Dysphagia was scored by partly blinded observers on a scale of 0–12 based on observations of eating (nonblinded), endoscopic examinations and fluoroscopic swallowing (blinded), where 0 = normal swallow and 12 = severe dysphagia with tracheal aspiration. Data were analysed by 3‐factor ANOVA, with significance taken as P<0.05. Results: Dysphagia models were reversible, and horses swallowed normally within 3 h of model induction. The marked dysphagia model impaired movement of feed from the base of the tongue to the oesophagus and caused severe airway contamination. The average dysphagia score (mean ± s.d.) for the marked dysphagia model was 10.6 ± 1.1 before surgery and 6.1 ± 4.3 after surgery (P = 0.007). Laryngeal advancement surgery did not significantly improve the dysphagia scores in the moderate model (P = 0.5). Conclusions: Laryngeal advancement surgery may improve swallowing and reduce aspiration in horses affected with diseases that cause pharyngeal dysphagia.